2022
DOI: 10.3847/1538-3881/ac69e3
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Neptune from TESS and CHEOPS Around the 120 Myr Old AB Dor Member HIP 94235

Abstract: The Transiting Exoplanet Survey Satellite (TESS) mission has enabled discoveries of the brightest transiting planet systems around young stars. These systems are the benchmarks for testing theories of planetary evolution. We report the discovery of a mini-Neptune transiting a bright star in the AB Doradus moving group. HIP 94235 (TOI-4399, TIC 464646604) is a V mag = 8.31 G-dwarf hosting a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 146 publications
(168 reference statements)
0
4
0
Order By: Relevance
“…Another close binary HIP 94235 (a ∼ 50 au) is consistent with the possibility that the primary hosts a transiting mini-Neptune. The companion HIP94235B exhibits an inclination of around 68° ( Zhou et al 2022), which suggests a minimum misalignment of 22°between the companions and the transiting planet. Given that HIP 94235 is part of a young comoving group (∼120 Myr, Zhou et al 2022), it is possible that the realignment between the companion and the disk is still ongoing.…”
Section: Implication For Planet Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Another close binary HIP 94235 (a ∼ 50 au) is consistent with the possibility that the primary hosts a transiting mini-Neptune. The companion HIP94235B exhibits an inclination of around 68° ( Zhou et al 2022), which suggests a minimum misalignment of 22°between the companions and the transiting planet. Given that HIP 94235 is part of a young comoving group (∼120 Myr, Zhou et al 2022), it is possible that the realignment between the companion and the disk is still ongoing.…”
Section: Implication For Planet Formationmentioning
confidence: 99%
“…The companion HIP94235B exhibits an inclination of around 68° ( Zhou et al 2022), which suggests a minimum misalignment of 22°between the companions and the transiting planet. Given that HIP 94235 is part of a young comoving group (∼120 Myr, Zhou et al 2022), it is possible that the realignment between the companion and the disk is still ongoing. Alternatively, it is also possible that the LTT 1445 BC was initially aligned with the primary disk from the onset.…”
Section: Implication For Planet Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…TESS has already detected and characterized tens of young planetary systems (e.g., Newton et al 2019;Battley et al 2020;Plavchan et al 2020;Zhou et al 2022;Wood et al 2023), providing initial insights into the differences between young planetary systems and their mature counterparts. Initial investigations into the population of young planets observed by TESS span a wider age range (Fernandes et al 2023), targeting clusters which already have confirmed planets (Fernandes et al 2022), and explored methods of light-curve extraction that best preserve transit signals in the scenario of heightened photometric variability from stellar activity (Nardiello et al 2020).…”
Section: Introductionmentioning
confidence: 99%